PENGARUH KEBUTUHAN PRIBADI, KELEMAHAN LINGKUNGAN PENGENDALIAN INTERNAL DAN KARAKTER PEGAWAI TERHADAP INTENSI PENGGUNA ANGGARAN DI PEMERINTAH PROVINSI KALIMANTAN SELATAN - Fendry Mappariza; Novita Weningtyas Respati; Fatimah (UIN Sunan Kalijaga, 2023)
The existence of indications of fraud on capital expenditure in the South Kalimantan provincial government is considered contrary to the decree of the governor of South Kalimantan number 188./44/0854/KUM/2020 regarding the appointment of Budget users of regional work units within the South Kalimantan provincial government for Fiscal Year 2021 regarding the duties, functions and powers of Budget users is evidence that budget users have not carried out their duties, functions and powers properly. This study was conducted to examine and analyze the influence of Personal Needs on the intention of Budget users on capital expenditure fraud. The effect of the weakness of the Local Government Internal control environment on the intention of Budget users on capital expenditure fraud. The influence of employee character on the intention of Budget users on capital expenditure fraud. This type of research is quantitative by survey method. The data analysis technique used is SEM-PLS with SmartPLS software. The population in this study is the official PA (budget users) of each SKPD South Kalimantan provincial government amounted to 165 with a sample of budget users in the Government of South Kalimantan. The result of this research is that personal needs influence the intention of budget users to commit fraud proved to be supported and accepted. The weakness of the internal control environment affects the intention of budget users commit fraud proved to be unsupported and rejected. Employee character affects the intention of budget users to commit fraud has been proven to be supported and accepted.